Contribution of Product, Price, Place, Promotion, and People (5P) Marketing Mix Strategy on Patients’ Interest To Revisit - Sri Ulina, Evita; Ginting, Chrismis Novalinda; Siregar, Santy Deasy (Universitas Padjadjaran, 2024)
In the National Health Insurance (JKN) era, hospitals in Indonesia rapidly grew in number and also developed. In order to stand out amongst the competition, hospitals often rely on marketing strategies through attractive advertisements, offering unique services, and also introducing their services to the public. One method often utilized in the 5P marketing mix consists of product, price, place, promotion, and people. This study aims to identify the impact of 5P marketing mix strategies on the patients’ interest in visiting Bandung Hospital in the city of Medan. Bandung Hospital in Medan conducted this quantitative study using a cross-sectional approach. This study involved 150 patients of Bandung Hospital’s inpatient unit, which is the whole outpatient clinic patient (total sampling) during the May 2023 period. Analysis was carried out using frequency distribution, chi-square, and binomial logistic regression analysis. This study found that the majority of patients visiting Bandung Hospital belong to the 30-39 years age group (62.0%), are female (58.7%), hold a bachelor's degree (48.0%), and are visiting Bandung Hospital for the first time (62.7%). Most of the patients in this study have a good perception toward all aspects of 5P marketing strategies in Bandung Hospital and are interested in visiting the hospital again in the future (p<0.05), with place playing the biggest role in influencing patients’ interest (OR = 4.082). According to all findings in this study, it can be concluded that marketing strategies such as the 5P marketing mix strategy positively influence patients’ interest in visiting Bandung Hospital. It can also be inferred that this strategy would work in similar types of hospitals, not only in Bandung Hospital. Keywords: Marketing mix, Hospital, Product-Price-Place-Promotion-People (5P), Patients